Human Resource Practices for Job Satisfaction:A Study on Public Sector Universities of Pakistan - Khan, Anum Afzal; Hashim, Muhammad; Najam, Suman; Maeenuddin,; Khudai, Muhammad Salman; Khan, Ahmad Imran (The journal of contemporary issues in business and government, 2021)
The success of the employee has an impact on morale when implemented in the best way possible. Organizational behavior studies pay close attention to motivation, the work satisfaction of workers and their effect on organizational performance. Several studies have been performed to research the impact of motivators on the satisfaction of employees. The goal of this analysis is to evaluate the impact on organization’s efficiency of motivators (combined effect and component effect). Also analyzed is the mediating role of work satisfaction between the drivers (combined impact and impact of components) and organizational efficiency. Data were obtained by self-administered survey by sampling all universities in the public sector of the Southern Punjab, Pakistan. To construct the questionnaire, likert scale has been used. In addition, the data analysis was based on different statistical methods. Studies have shown that the motivator (combined effect and component effect) have a clear and positive relationship with the organizational efficiency. More work satisfaction as mediator has a direct influence on the success of organizations between motivators (combined effect and effect of components).